'Entirely free and at liberty to engage their services as they may think fit'? Recaptured African Adjudication and Freedom at the Cape Colony, 1806-1834 - Crous, Benjamin (Journal of southern African studies, 2025)
Between 1806 and 1834, approximately 2,600 recaptured Africans arrived on the shores of the British-controlled Cape Colony. Seized and embarked on slave ships, these individuals had been captured by anti-slavery squadrons and taken back to their British base. Recaptives were then 'freed' by Vice Admiralty Courts and apprenticed to colonists for periods of between seven and 14 years. During these apprenticeships, they were supposed to be instructed in employable skills to sustain them when they became free. While much scholarship has focused on the process of liberation of the Cape's enslaved people, no attention has yet been paid to the life trajectories of recaptured Africans. Using nominal linkage between quantitative sources such as the Cape's annual tax census, as well as the archives of the 1820s Commission of Eastern Inquiry, this article traces this journey of adjudication, apprenticeship and freedom as best as the existing sources allow. The research uncovers a new bourgeois class of Cape colonists benefiting substantially from the dishonest distribution of recaptives by corrupt collector of customs Charles Blair. Furthermore, it charts the opportunities available to recaptives ending their apprenticeships. This post-apprenticeship environment was complex and shaped by a variety of factors, including the nature of and their understanding of their new contracts, relationship with their contract holders, police harassment and available land and accommodation.